Marine Pollution Mitigation by Waste Oils Recycling Onboard Ships: Technical Feasibility and Need for New Policy and Regulations - Mazzoccoli, Michela; Altosole, Marco; Vigna, Veronica; Bosio, Barbara; Arato, Elisabetta (Frontiers in Marine Science, 2020)
About 80% of the total pollution from ships is caused by operational oil discharges into the sea, often made deliberately and in violation of international rules; the main reasons can be due to cost savings or lack of adequate facilities in ports to receive waste oils. Therefore, reducing waste oils discharges is crucial for a proper protection of the marine environment. In this regard, the paper presents the preliminary feasibility of a particular waste recycling technology, aimed at obtaining marine fuel oil from sludge, through a pyrolysis process to be carried out in a small reactor onboard. Although the preliminary lab tests and simulation results in the chemical process are enough promising, there are still some technical criticalities due to the energy optimization of the reactor for an efficient use onboard of the whole system. In addition, the possibility of recycling waste, directly onboard ships, is not yet covered by mandatory regulations, which is why shipowners generally still feel unmotivated to invest in such technologies.